A Comment on Alesina, Miano and Stancheva (2023) - Sabina Albrecht; Jason Collins; Romain Gauriot; Fannie Wu (Institute for Replication (I4R), 2023)
Alesina et al. (2023) examine how people perceive the number and characteristics of migrants and how those perceptions affect their support for redistribution. They find that respondents from the United States, United Kingdom, Sweden, Italy, Germany and France markedly overestimate the share of immigrants in each country, with the average respondent in all countries except Sweden overestimating by more than a factor of two. We reproduce these results using the original code and data and test the robustness by (i) including participants excluded for time to complete the survey, (ii) extending the analysis of misperceptions to all survey respondents, and (iii) using alternative authoritative estimates of the proportion of immigrants. We find that these checks marginally change the estimates of the size of the misperception but do not change the conclusions to be drawn from the analysis. Alesina et al. (2023) also test the effect on support for redistribution of showing videos on immigrant characteristics. We computationally reproduced the treatment effects on support for redistribution.
Keywords: 330